Peridynamic model for tensile elongation and fracture simulations of polymethyl methacrylate notched specimens - Azizi, Muhammad Azim; Mohd Ridhuan, Mohd Faiz; Mohd Zahari, Mohd Zakiyuddin; Abdul Rahim, Sharafiz; Azman, Muhammad Amin (Trans Tech Publications, 2022)
This paper presents the peridynamic (PD) numerical model for simulating a tensile test until total fracture for a brittle polymeric material namely polymethyl methacrylate (PMMA). U-notched and V-notched specimens were used to investigate the effect of the notches on the elongation and fracture of PMMA. The tensile elongation of PMMA exhibits nonlinearity with respect to the applied load, while the fracture occurs when the material stress has reached the ultimate tensile stress of the material. Similar elongation and fracture properties were applied on PD simulations. Two types of elongation equation are used namely brittle and ductile equations to form PD-brittle and PD-ductile models. The published experimental data of tensile fracture test on notched PMMA specimens are used as reference to validate the simulations of the PD models. The PD numerical force-extension curves have good quantitative similarity for V-notched specimen but adequate quantitative similarity for U-notched specimen. As for the quality of the fractured specimen shape, the PD simulations have good similarity for the V-notched specimen but adequate similarity for the U-notched specimen. The plot of the internal force distribution from the simulations of PD shows good qualitative similarity to the plot of the stress distribution from the published data of FEM in terms of stress concentration. From the PD results, it is observed that the PD-ductile model has better capability in producing accurate simulation of the notched specimens than the PD-brittle model.